Chloramphenicol induced maculopapular rashes - Wadagbalkar, Prashant; Patel, Poonam (International Journal of Basic & Clinical Pharmacology, 2017)
Chloramphenicol is a broad spectrum antibiotic that acts by inhibiting protein synthesis. Though systemic use is rare, their topical preparations are commonly used. Allergic reaction due to chloramphenicol ear drops are less reported. Here, we have reported a maculopapular exanthema due to use of chloramphenicol ear drops.